2006
DOI: 10.1158/0008-5472.can-05-3521
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Imaging Using a Picomolar Affinity HER2 Binding Affibody Molecule

Abstract: The detection of cell-bound proteins that are produced due to aberrant gene expression in malignant tumors can provide important diagnostic information influencing patient management. The use of small radiolabeled targeting proteins would enable high-contrast radionuclide imaging of cancers expressing such antigens if adequate binding affinity and specificity could be provided. Here, we describe a HER2-specific 6 kDa Affibody molecule (hereinafter denoted Affibody molecule) with 22 pmol/L affinity that can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
516
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 484 publications
(540 citation statements)
references
References 40 publications
21
516
2
1
Order By: Relevance
“…When comparing the binding of the bs affibody molecule to the binding of the parental dimeric (Z HER2:342 ) 2 and (Z EGFR:1907 ) 2 proteins used as controls (Figures 2A and 2B), the bs affibody protein showed a similar binding profile as the (Z HER2:342 ) 2 when injected over the HER2 surface (Figure 2A). A retained high association rate and a low dissociation rate was demonstrated, in accordance with previous data for Z HER2:342 [30]. The decrease in binding to HER2 during the first seconds of the dissociation phase is likely to be due to differences in the buffer, but it does not influence the low dissociation rate.…”
Section: Single and Dual Binding Biosensor Analysissupporting
confidence: 90%
See 4 more Smart Citations
“…When comparing the binding of the bs affibody molecule to the binding of the parental dimeric (Z HER2:342 ) 2 and (Z EGFR:1907 ) 2 proteins used as controls (Figures 2A and 2B), the bs affibody protein showed a similar binding profile as the (Z HER2:342 ) 2 when injected over the HER2 surface (Figure 2A). A retained high association rate and a low dissociation rate was demonstrated, in accordance with previous data for Z HER2:342 [30]. The decrease in binding to HER2 during the first seconds of the dissociation phase is likely to be due to differences in the buffer, but it does not influence the low dissociation rate.…”
Section: Single and Dual Binding Biosensor Analysissupporting
confidence: 90%
“…The dimer format of each affibody molecule in the bs affibody protein will most likely give an additional increase in functional affinity (avidity), as demonstrated previously [38,39]. Furthermore, high selectivity of the Z HER2:342 and Z EGFR:1907 affibody molecules to their respective target protein has been shown in previous studies [30,39]. In the present study, binding to HER2 and EGFR was confirmed for the bs affibody protein (Figure 2).…”
Section: Single and Dual Binding Biosensor Analysissupporting
confidence: 86%
See 3 more Smart Citations